Preparation and application of sandwich type {Ni (P4Mo6)} multi-acid-group three-dimensional crystalline material

Sandwich {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material was prepared by one-step hydrothermal synthesis, which solved the problem of poor conductivity and stability of polyacid polymers in acidic solutions, and achieved efficient electrocatalytic nitric acid Root reduction and stable ammonia synthesis demonstrate excellent catalytic performance and stability.

CN119433715APending Publication Date: 2025-02-14HARBIN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411387554.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-04
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

As an electrocatalytic nitrate reduction catalyst, polyacid polymers have poor conductivity and stability in acidic solutions, which affects their synthesis of ammonia.

Method used

Sandwich type was prepared by a one-step hydrothermal synthesis method using 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10) orthodiazaphene organic ligand using 2-(4-(4-carboxyphenyl)phenyl)amino(4,5-f)(1,10) orthodiazaphene organic ligand. {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material forms a polyacid-based metal organic framework structure to improve its electrocatalytic activity.

Benefits of technology

Achieved the ammonia production at voltage -0.5V vs.RHE, with a maximum Faraday efficiency of 99.5%, and the current density, ammonia production and Faraday efficiency were maintained in the 12h stability test. Stability, proves that the material has excellent stability and catalytic properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005071371020000022
    Figure BDA0005071371020000022
  • Figure BDA0005071371020000061
    Figure BDA0005071371020000061
  • Figure FDA0005071371010000012
    Figure FDA0005071371010000012
Patent Text Reader

Abstract

The invention relates to preparation and application of a sandwich type {Ni (P4Mo6)} multi-acid-group three-dimensional crystalline material. The invention aims to solve the problems of insufficient conductivity and active sites of some multi-acid-group metal organic framework crystalline-state materials serving as electro-catalysis nitrate reduction catalysts in an acid solution, and provides a preparation method of a nitrate synthesis ammonia electro-catalysis material capable of improving the internal electron transmission capability. The chemical formula of the sandwich type {Ni (P4Mo6)} multi-acid-group three-dimensional crystalline material is (HNCP) 4 [Ni (H2O) 3] 7 [NiMo12 (H2PO4) 6 (PO4) 2 (OH) 6O24], and the HNCP is 2-(4-(4-carboxyl phenyl) phenyl) imidazo (4, 5-f) (1, 10) phenanthroline. The synthesis method comprises the following steps: adding sodium molybdate, nickel chloride and HNCP into ethanol and distilled water, uniformly stirring, adjusting the pH value, and reacting for 3 days at the temperature of 160 DEG C. In a low-concentration acidic electrolytic solution, the highest ammonia yield and Faraday efficiency of an electrocatalytic material prepared from the obtained polymer are 4.96 mg h <-1 > mg <-1 > cat and 99.5% respectively. A technical route is provided for constructing a high-dimension multi-acid-group metal organic framework crystalline material as a nitrate radical reduction catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the preparation and application of a sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material. Background Art

[0002] In recent years, ammonia has attracted widespread attention as an emerging alternative fuel for vehicles and a potential hydrogen storage medium. Although the Haber process contributes 90% of the world's annual ammonia production, the harsh synthesis conditions and large amounts of greenhouse gas emissions make it difficult to meet the development requirements of the green economy. In order to seek a mild and sustainable alternative process for synthesizing ammonia, people have successively invented a variety of nitrogen fixation processes including simulated biological nitrogenase, photocatalysis, and electrocatalysis. Among them, electrocatalytic nitrate reduction to synthesize ammonia, which uses nitrate as raw material, is driven by electricity and avoids the use of expensive and toxic reagents, has become a synthetic ammonia process sought after by scientific researchers in recent years.

[0003] Polyoxometalates, or polyoxometalates (POMs), are a class of nanometallic oxygen cluster compounds with clear structures and adjustable compositions. At the same time, polyoxometalates have many special properties, such as diverse compositions, reversible redox properties, high thermal stability, and semiconductor-like optical properties, which make them show broad application prospects in the fields of catalysis, materials, light, and electricity. Among the many types of polyoxometalates, [P4Mo6O 31 ] 12- , abbreviated as {P4Mo6}, is one of the most readily available polyoxometalates. The {P4Mo6} anion has a stable structure, small steric hindrance and abundant active oxygen atoms. However, the strong water solubility and poor conductivity of polyoxometalates inhibit their application in the field of electrocatalytic nitrate reduction.

[0004] Polyacid-based metal-organic frameworks (POMOFs) are polyacids introduced into metal-organic frameworks (MOFs). POMOFs combine the advantages of POMs and MOFs, with the diverse coordination modes, regular structures, orderly arranged organic ligands of MOFs and the redox and electron-rich properties of POMs, and can effectively overcome the disadvantage of POMs being soluble in water. Through reasonable design, when POMOFs are used for electrocatalytic reactions, POMs can provide electrons for the catalytic active sites of metal ions and promote the electron transfer process inside POMOFs, which is expected to show more promising electrocatalytic activity in the electrocatalytic reduction of nitrates to synthesize ammonia. Therefore, with {P4Mo6} as the skeleton structural unit, metals and organic matter are introduced, and the polyacid-based metal-organic framework structure is easily formed by inducing the coordination of metal cations with them. At the same time, {P4Mo6} can also serve as an electron reservoir to directly provide electrons to metal ions, realize the rapid activation of metal ion catalytic centers, and improve catalytic performance. Based on the good application prospects of polyacid-based metal-organic framework crystalline materials, we have studied and prepared a new sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material with electrocatalytic nitrate reduction performance that has not been reported in the literature. Summary of the invention

[0005] The purpose of the present invention is to solve the problem that some polyacid polymers have poor conductivity and stability in acidic solutions as electrocatalytic nitrate reduction catalysts. In order to improve its ammonia synthesis performance, the present invention provides a preparation method and application of a sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material.

[0006] In order to solve the above technical problems, the present invention is achieved through the following technical solutions:

[0007] 1. preparing a reaction solution with a pH value of 3.8 to 4.0: adding sodium molybdate, nickel chloride and 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)phenanthroline to ethanol and distilled water and stirring evenly, and then adjusting the pH value of the suspension to 3.8 to 4.0 to obtain a reaction solution with a pH value of 3.8 to 4.0;

[0008] The molar ratio of sodium molybdate to nickel chloride in step 1 is 1:0.75;

[0009] The molar ratio of sodium molybdate to 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)phenanthroline in step 1 is 1:0.04;

[0010] The volume ratio of the amount of sodium molybdate described in step 1 to ethanol and distilled water is: 0.41mmol:1mL:4mL;

[0011] 2. The reaction solution prepared in step 1 was transferred to a polytetrafluoroethylene reactor and reacted at 160°C for 3 days. The reaction solution was cooled to room temperature and then washed to obtain yellow-brown rectangular crystals, i.e., sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline materials. The chemical formula of the polymer is (HNCP)4[Ni(H2O)3]7[NiMo 12 (H2PO4)6(PO4)2(OH)6O 24 ], where HNCP is 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)phenanthroline; the crystal appearance is yellow-brown cuboid; the crystal system is triclinic; the space group is Pī; the unit cell parameters are α=101°, β=98°, γ=113°,

[0012] 3. Preparation of sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material electrocatalytic nitrate reduction electrode: Grind 20 mg of three-dimensional polyacid-based nickel organic framework crystalline material and 20 mg of acetylene black evenly, take 3 mg of the ground sample and add it to 125 μL of isopropanol, 10 μL of Nafion solution and 365 μL of water, and ultrasonicate for 2 hours to obtain a uniformly dispersed mixed solution. Take 10 μL of the mixed solution and drop it on the pretreated carbon cloth. After standing at room temperature for 10 hours, a working electrode modified with a sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material is obtained.

[0013] Compared with the prior art, the present invention has the following beneficial effects:

[0014] 1. The present invention uses 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)phenanthroline organic ligand for the first time, and successfully prepares a polyacid-based metal organic framework crystalline material by a one-step hydrothermal synthesis method with sodium molybdate and nickel chloride. Single crystal X-ray diffraction results show that the crystalline material prepared by the present invention is a three-dimensional polyacid-based nickel organic framework crystalline material. Among them, the polyacid in the polymer molecule constructs a one-dimensional chain structure vertically, and at the same time, the polyacid and the organic ligand extend along a plane perpendicular to the vertical axis with metal ions as the connection point, and form a three-dimensional framework structure through the interaction of a large number of chemical bonds.

[0015] 2. A sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material prepared in this embodiment is used as an electrocatalytic nitrate reduction catalyst. When the voltage is -0.3, -0.4, -0.5, -0.6, -0.7 and -0.8 V vs. RHE, the working electrode is tested for nitrate reduction. Figure 7 As shown in Figure 2, in a 0.1M NaNO3 / 0.05M H2SO4 solution, at -0.5V vs. RHE, the ammonia production was 4.96mg h-1 mg -1 cat. The maximum Faraday efficiency is 99.5%. The stability test was carried out in 0.1M NaNO3 / 0.05M H2SO4 electrolyte for 12h. Figure 8 As shown, after 12 h of continuous electrolysis, the current density, ammonia production and Faraday efficiency remained stable, proving that the polymer has excellent stability.

[0016] The excellent catalytic effect is mainly based on the following reasons: 1. In this polyacid-based complex constructed with reductive phosphomolybdic acid {P4Mo6}, metal Ni and reductive phosphomolybdic acid {P4Mo6} can play a synergistic role to promote the reduction of nitrate; 2. The π-π bond of the aromatic ligand HNCP can promote electron transfer, which is beneficial to the improvement of the conductivity of the polyacid-based complex constructed with reductive phosphomolybdic acid {P4Mo6}; 3. The three-dimensional framework structure formed by {P4Mo6}, metal ions and organic ligands effectively promotes electron transfer inside the catalyst and improves the performance of the material in electrocatalytic synthesis of ammonia. This method provides a research model for the electrocatalytic nitrate synthesis of ammonia by polyacid-based complexes. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is an example - a diagram of the basic structural unit of a sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material.

[0018] Figure 2 This is an example - a schematic diagram of the connection structure of a sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material.

[0019] Figure 3 This is an example - a schematic diagram of the three-dimensional structure of a sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material.

[0020] Figure 4 This is the infrared spectrum of the embodiment - sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material.

[0021] Figure 5 This is the powder X-ray diffraction pattern of the embodiment - sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material.

[0022] Figure 6 This is an example - a sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material is used as a working electrode, and the ultraviolet-visible light absorption spectrum is plotted at different voltages in a 0.1MNaNO3 / 0.05M H2SO4 electrolyte.

[0023] Figure 7For example, a sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material is used as a working electrode. The ammonia production and Faraday efficiency are shown in 0.1MNaNO3 / 0.05M H2SO4 electrolyte when the voltages are -0.3, -0.4, -0.5, -0.6, -0.7 and -0.8 V vs. RHE, respectively.

[0024] Figure 8 For example, a sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material was used as a working electrode. When the voltage was -0.5V vs. RHE in a 0.1MNaNO3 / 0.05M H2SO4 electrolyte, the time-current curve for 12 hours and the ammonia production and Faraday efficiency diagram of 12 cycle reactions were continuously tested. DETAILED DESCRIPTION

[0025] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention that does not depart from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.

[0026] Specific implementation method 1: This implementation method describes a sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material, the molecular formula of the polymer is C 80 Mo 12 N 16 Ni8O 96 P8, its basic structural unit contains eight Ni metal ions, one {P4Mo6}, and one HNPC; the nickel ion has six coordination environments, Ni1 is a six-coordination mode, composed of two polyacids each providing three bridging oxygens in Mo-O-Mo; Ni2 is also a six-coordination mode, composed of two N in the ligand, three coordinated water molecules and oxygen atoms of the polyacid; Ni3 is a five-coordination mode, composed of two N in the ligand, two coordinated water and PO terminal oxygen in the polyacid. Ni4 is a three-coordination mode, composed of two coordinated water molecules and another oxygen atom of the polyacid; Ni5 is a six-coordination mode, composed of two polyacids each providing two PO terminal oxygens and metal oxygen. At the same time, Ni3, Ni5 and Ni6 serve as connection points to extend the polyacid along the a-axis to form a one-dimensional long chain structure; Ni2, Ni2b, Ni2c and Ni2d serve as connection points to extend the polyacid along the b-axis and c-axis planes to form a three-dimensional spatial structure.

[0027] Specific implementation method 2: A method for preparing a sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material in this implementation method is completed by the following steps:

[0028] 1. Prepare a reaction solution with a pH value of 3.8 to 4.0: add 0.17 g of sodium molybdate, 0.08 g of nickel chloride and 0.01 g of 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)phenanthroline to ethanol and distilled water and stir evenly, then adjust the pH value of the suspension to 3.8 to 4.0 to obtain a reaction solution with a pH value of 3.8 to 4.0;

[0029] The molar ratio of sodium molybdate to nickel chloride in step 1 is 1:0.75;

[0030] The molar ratio of sodium molybdate to 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)phenanthroline in step 1 is 1:0.04;

[0031] The volume ratio of the amount of sodium molybdate described in step 1 to ethanol and distilled water is: 0.41mmol:1mL:4mL;

[0032] 2. Preparation of sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material: The reaction solution prepared in step 1 was transferred to a polytetrafluoroethylene reactor and then reacted at 160°C for 3 days. The reaction solution was cooled to room temperature and then washed to obtain yellow-brown rectangular crystals, i.e., sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material. The polymer chemical formulas are (HNCP)4[Ni(H2O)3]7[NiMo 12 (H2PO4)6(PO4)2(OH)6O 24 ], where HNCP is 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)phenanthroline; the crystal appearance is yellow-brown cuboid; the crystal system is triclinic; the space group is Pī; the unit cell parameters are α=101°, β=98°, γ=113°,

[0033] 3. Preparation of a sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material electrocatalytic nitrate reduction electrode: Grind 20 mg of three-dimensional polyacid-based nickel organic framework crystalline material and 20 mg of acetylene black evenly, take 3 mg of the ground sample and add it to 125 μL of isopropanol, 10 μL of Nafion solution and 365 μL of water, and ultrasonicate for 2 hours to obtain a uniformly dispersed mixed solution. Take 10 μL of the mixed solution and drop it on the pretreated carbon cloth. After standing at room temperature for 10 hours, a sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material modified working electrode was obtained, which was used to test the nitrate reduction performance.

[0034] The carbon cloth described in step three needs to be pretreated. The specific process is: first, soak it in acetone solution for 30 minutes, then ultrasonically soak it in anhydrous ethanol and deionized water for 3 times, each ultrasonic time is 30 minutes, and finally, completely immerse the carbon cloth in concentrated nitric acid, put it in a reactor, and react it at 120°C for 2 hours. After cooling to room temperature, wash it with deionized water until the pH is neutral, and then the carbon cloth can be used. At the same time, the electrochemical test selects a three-electrode system, with the modified glassy carbon electrode as the working electrode, the silver / silver chloride electrode as the reference electrode, and platinum as the counter electrode.

[0035] Specific implementation method three: Specific implementation method two step one of the preparation method of the sandwich type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material, the molar ratio of sodium molybdate, nickel chloride, and 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)phenanthroline is 1:0.75:0.36.

[0036] Specific embodiment 4: This embodiment differs from specific embodiment 2 in that the metal nickel salt in step 1 is nickel acetate, nickel nitrate or nickel sulfate. The rest is the same as specific embodiments 1 to 3.

[0037] Specific implementation method five: Specific implementation method two step one of the method for preparing the sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material, the volume ratio of the amount of sodium molybdate to ethanol and distilled water is: 0.41mmol:1mL:4mL.

[0038] Specific embodiment 6: The difference between this embodiment and specific embodiment 2 is that the pH value of the reaction solution is adjusted to 3.8-4.0 in step 1 by using H3PO4 solution and NaOH solution with molar concentrations of 1 mol / L. The other steps are the same as those of specific embodiments 1 to 5.

[0039] Specific embodiment 7: The difference between this embodiment and specific embodiment 2 is that the reaction temperature in step 2 is 160° C. and the reaction time is 3 days. The other steps are the same as those in specific embodiments 1 to 6.

[0040] Specific embodiment eight: the mass of the prepared phosphomolybdic acid crystalline material, acetylene black, and the volume ratio of isopropanol to distilled water described in step three of specific embodiment two are 1.5 mg: 1.5 mg: 0.125 mL: 0.365 mL.

[0041] The following examples are used to verify the beneficial effects of the present invention:

[0042] Embodiment - Preparation method of sandwich type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material, according to the following steps:

[0043] 1. Prepare a reaction solution with a pH value of 3.8: evenly disperse 0.83 mmol of sodium molybdate, 0.62 mmol of nickel chloride and 0.03 mmol of 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)phenanthroline in a mixed solution of 10 mL of ethanol and 40 mL of distilled water, and then adjust the pH value of the reaction solution to 3.8 using 1 mol / L H3PO4 solution and 1 mol / L NaOH solution to obtain a reaction solution with a pH value of 3.8.

[0044] The molar ratio of sodium molybdate to nickel chloride in step 1 is 1:0.75;

[0045] The molar ratio of sodium molybdate to 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)phenanthroline in step 1 is 1:0.04;

[0046] The volume ratio of the amount of sodium molybdate described in step 1 to ethanol and distilled water is: 0.41mmol:1mL:4mL;

[0047] 2. The prepared reaction solution with a pH value of 3.8 was transferred to an 80 mL polytetrafluoroethylene reactor, and then reacted at a temperature of 160°C for 3 days. The reaction solution was cooled to room temperature and then washed to obtain yellow-brown rectangular crystals, which are polyacid-based nickel organic framework crystalline materials with a three-dimensional spatial structure.

[0048] (I) Structural determination of the sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material prepared in Example 1:

[0049] Conclusion ① X-ray crystallography parameters: see Table 1.

[0050] Table 1 Crystallographic parameters of materials

[0051]

[0052] a R1=∑║F o │─│F c ║ / ∑│F o │. b wR2={∑[w(F o 2 ─F c 2 ) 2 ] / ∑[w(F o 2 ) 2 ]} 1 / 2

[0053] Conclusion②X-ray crystal structure description: X-ray single crystal diffraction analysis shows that

[0054] The sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material is a triclinic system. Space group. The unit cell parameters are α=101°, β=98°, γ=113°, like Figure 1 As shown in Figure 2, the polymer includes eight Ni metal ions, one {P4Mo6}, and one HNPC. Figure 2 As shown, there are six chemical states of Ni atoms, Ni1 is a hexacoordinate mode, composed of two polyacids each providing three bridging oxygens in Mo-O-Mo; Ni2 is also a hexacoordinate mode, composed of two N in the ligand, three coordinated water molecules and oxygen atoms of the polyacid; Ni3 is a pentacoordinate mode, composed of two N in the middle ligand, two coordinated water and the PO terminal oxygen in the polyacid. Ni4 is a tricoordinate mode, composed of two coordinated water molecules and another polyacid oxygen atom; Ni5 is a hexacoordinate mode, composed of two polyacids each providing two PO terminal oxygens and metal oxygen. At the same time, Ni3, Ni5 and Ni6 serve as connection points to extend the polyacid along the a-axis to form a one-dimensional long chain structure; Ni2, Ni2b, Ni2c and Ni2d serve as connection points to extend the polyacid along the b-axis and c-axis planes to form a three-dimensional spatial structure (such as Figure 3 shown).

[0055] Figure 1 This is an example - a diagram of the basic structural unit of a sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material.

[0056] Figure 2 This is an example - a schematic diagram of the connection structure of a sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material.

[0057] Figure 3 This is an example - a schematic diagram of the three-dimensional structure of a sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material.

[0058] (ii) Example - Sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material (HNCP)4[Ni(H2O)3]7[NiMo 12 (H2PO4)6(PO4)2(OH)6O 24 ] to perform infrared spectroscopy characterization to obtain the infrared spectrum of the polyacid-based nickel organic framework crystalline material. Figure 4 As shown, at 1075, 966, 816 and 736 cm -1 The characteristic peaks are attributed to ν(PO), ν(Mo=Ot), ν(Mo-Ob-Mo) and ν(Mo-Oc-Mo) stretching vibrations; the vibration peaks are between 1100 and 1700 cm-1 The range is attributed to organic ligands, at 3450cm -1 The peak at 1021cm is attributed to the stretching vibration of water molecules in the compound. -1 The characteristic peak at is attributed to the stretching vibration of Ni-N in the crystal structure.

[0059] Figure 4 This is an infrared spectrum of the three-dimensional polyacid-based nickel organic framework crystalline material of Example.

[0060] (III) Example - Sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material (HNCP)4[Ni(H2O)3]7[NiMo 12 (H2PO4)6(PO4)2(OH)6O 24 ] to perform powder X-ray diffraction measurement to obtain a powder X-ray diffraction spectrum of the polyacid-based nickel organic framework crystalline material. Figure 5 As shown, the peak positions of the experimentally measured spectrum and the spectrum obtained by crystal simulation are consistent. It can be determined that the crystal structure obtained by the experiment is the structure analyzed by the software, and the purity of the crystal is very high.

[0061] Figure 5 This is the powder X-ray diffraction pattern of the embodiment - sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material.

[0062] (IV) Example - Sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material (HNCP)4[Ni(H2O)3]7[NiMo 12 (H2PO4)6(PO4)2(OH)6O 24 ] to test the electrochemical performance. A three-electrode system was used, with a glassy carbon electrode as the working electrode, a silver / silver chloride electrode as the reference electrode, and platinum as the counter electrode. The electrochemical time-current curve of the polymer was tested at different voltages in a 0.1M NaNO3 / 0.05M H2SO4 electrolyte. After measuring for 1 hour, 10mL of the electrolyte in the anode electrolytic cell was taken for color development and tested using a UV spectrophotometer. Figure 6 As shown in the figure, at -0.6V vs.RHE, the three-dimensional polyacid-based nickel organic framework crystalline material has a high absorbance, indicating that the complex has good electrocatalytic nitrate reduction properties at -0.6V vs.RHE voltage. The working electrode was tested for nitrate reduction at voltages of -0.3, -0.4, -0.5, -0.6, -0.7 and -0.8V vs.RHE. Figure 7 As shown in Figure 2, at -0.5 V vs. RHE, the Faraday efficiency of the polymer is 99.5% at most, and the ammonia production is 4.96 mg h -1 mg -1cat. At -0.6V vs. RHE, the ammonia production is the largest. The stability test was carried out in 0.1M NaNO3 / 0.05M H2SO4 electrolyte for 12h. Figure 8 As shown, after 12 h of continuous electrolysis, the current density, ammonia production and Faraday efficiency remained stable, proving that the polymer has excellent stability.

[0063] Figure 6 This is an example - a sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material is used as a working electrode, and the ultraviolet-visible light absorption spectrum is plotted at different voltages in a 0.1MNaNO3 / 0.05M H2SO4 electrolyte.

[0064] Figure 7 For example, a sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material is used as a working electrode. The ammonia production and Faraday efficiency are shown in 0.1MNaNO3 / 0.05M H2SO4 electrolyte when the voltages are -0.3, -0.4, -0.5, -0.6, -0.7 and -0.8 V vs. RHE, respectively.

[0065] Figure 8 For example, a sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material was used as a working electrode. When the voltage was -0.5V vs. RHE in a 0.1MNaNO3 / 0.05M H2SO4 electrolyte, the time-current curve for 12 hours and the ammonia production and Faraday efficiency diagram of 12 cycle reactions were continuously tested.

[0066] In summary: A sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material prepared in Example 1 was used for the electrocatalytic nitrate reduction reaction. The polymer has high catalytic activity for nitrate, and has excellent conductivity and stability. It is an electrocatalytic material with excellent performance and shows potential application value in the field of synthetic ammonia.

Claims

1. A sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material, whose chemical formula is (HNCP)4[Ni(H2O)3]7[NiMo 12 (H2PO4)6(PO4)2(OH)6O 24 ], where HNCP is 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)phenanthroline; the crystal appearance is yellow-brown cuboid; the crystal system is triclinic; the space group is Pī; the unit cell parameters are α=101°, β=98°, γ=113°, 2. A sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material, characterized in that Different from the structure of other types of phosphomolybdic acid polymers. There are eight Ni metal ions, one {P4Mo6}, and two HNPCs in its basic structural unit. There are six chemical states of Ni atoms. Ni1 is a six-coordinate mode, composed of two polyacids each providing three bridge oxygens in Mo-O-Mo; Ni2 is also a six-coordinate mode, composed of two N in the ligand, three coordinated water molecules and oxygen atoms of the polyacid; Ni3 is a five-coordinate mode, composed of two N in the ligand, two coordinated water and PO terminal oxygen in the polyacid. Ni4 is a three-coordinate mode, composed of two coordinated water molecules and another oxygen atom of the polyacid; Ni5 is a six-coordinate mode, composed of two polyacids each providing two PO terminal oxygens and metal oxygen. At the same time, Ni3, Ni5 and Ni6 are used as connection points to extend the polyacid along the a-axis to form a one-dimensional long chain structure; Ni2, Ni2b, Ni2c and Ni2d are used as connection points to extend the polyacid along the b-axis and c-axis planes to form a three-dimensional spatial structure.

3. The preparation method of sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material is completed by the following steps:

1. Prepare a reaction solution with a pH value of 3.8 to 4.0: add 0.17 g of sodium molybdate, 0.08 g of nickel chloride and 0.01 g of 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)phenanthroline to ethanol and distilled water and stir evenly, then adjust the pH value of the suspension to 3.8 to 4.0 to obtain a reaction solution with a pH value of 3.8 to 4.

0. The molar ratio of sodium molybdate to nickel chloride in step 1 is 1:0.75; The molar ratio of sodium molybdate to 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)phenanthroline in step 1 is 1:0.04; The volume ratio of the amount of sodium molybdate described in step 1 to ethanol and distilled water is: 0.41mmol:1mL:4mL.

2. Preparation of sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material: The reaction solution prepared in step 1 was transferred to a polytetrafluoroethylene reactor and then reacted at 160°C for 3 days. The reaction solution was cooled to room temperature and then washed to obtain yellow-brown rectangular crystals, i.e., three-dimensional polyacid-based nickel organic framework crystalline material. The polymer chemical formula of step 2 is (HNCP)4[Ni(H2O)3]7[NiMo 12 (H2PO4)6(PO4)2(OH)6O 24 ], where HNCP is 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)phenanthroline; the crystal appearance is yellow-brown cuboid; the crystal system is triclinic; the space group is Pī; the unit cell parameters are α=101°, β=98°, γ=113°, 4. The method for preparing a sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material according to claim 3, characterized in that The nickel chloride described in step 1 can be replaced by nickel acetate, nickel nitrate or nickel sulfate.

5. The method for preparing a sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material according to claim 3, characterized in that The molar ratio of sodium molybdate, nickel chloride, and 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)phenanthroline described in step 1 is 1:0.75:0.

36. Meanwhile, the structural formula of the organic ligand 2-(4-(4-carboxyphenyl)phenyl)imidazo(4,5-f)(1,10)phenanthroline described in step 1 is 6. The method for synthesizing a sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material according to claim 3, characterized in that The volume ratio of the amount of sodium molybdate described in step 1 to ethanol and distilled water is: 0.41mmol:1mL:4mL.

7. The method for synthesizing a sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material according to claim 3, characterized in that In the process of adjusting the pH value of the reaction solution to 3.8-4.0 in step 1, a H3PO4 solution with a molar concentration of 1 mol / L and a NaOH solution with a molar concentration of 1 mol / L are used for adjustment.

8. The method for preparing a sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material according to claim 3, characterized in that The reaction temperature in step 2 is 160° C. and the reaction time is 3 days.

9. Preparation of a sandwich-type {Ni(P4Mo6)} polyacid-based three-dimensional crystalline material electrocatalytic nitrate reduction electrode: Grind 20 mg of three-dimensional polyacid-based nickel organic framework crystalline material and 20 mg of acetylene black evenly, take 3 mg of the ground sample and add it to 125 μL of isopropanol, 10 μL of Nafion solution and 365 μL of water, ultrasonicate for 2 hours to obtain a uniformly dispersed mixed solution, take 10 μL of the mixed solution and drop it on the pretreated carbon cloth, let it stand at room temperature for 10 hours, and then obtain a working electrode modified with a three-dimensional polyacid-based nickel organic framework crystalline material, which is used to test the nitrate reduction performance.